The Correlates of Statistics Anxiety: Relationships With Spatial Anxiety, Mathematics Anxiety and Gender - Rose-Marie Gibeau; Erin A. Maloney; Sébastien Béland; Daniel Lalande; Michael Cantinotti; Alexandre Williot; Lucile Chanquoy; Jessica Simon; Marie-Aude Boislard-Pépin; Denis Cousineau (Journal of Numerical Cognition, 2023)
This study investigates the correlates of statistics anxiety. Considering that statistics anxiety and spatial anxiety have been separately correlated with related constructs (e.g., mathematics anxiety, academic performance, etc.), the possibility that spatial anxiety plays a role in statistics anxiety is explored. When facing statistics or mathematics operations, people may imagine or visualize the task operations they must do to obtain the result. To examine this hypothesis, 778 students in a Social or Health Sciences program, enrolled in a –often mandatory– statistics course from Canadian, French and Belgian universities completed an online survey. The results show moderate to strong positive correlations between all three types of anxiety (spatial, mathematics, and statistics). In addition, a mediation analysis reveals the intermediate role played by mathematics anxiety in the relationship between spatial and statistics anxieties. Nonetheless, the direct link from spatial anxiety to statistics anxiety is non-negligible in the model. Finally, the results also indicate that women report higher levels of statistics anxiety, which may be partly explained by their higher level of spatial anxiety.